Student study guide for use with Chemistry - Chang, Raymond (Mc-Graw Hill, 2005)
The "Student Solutions Manual" will have all the solutions to the even numbered problems in the text. The style of the solutions will match worked examples in the text to help the student learn how to solve the problems